The Spleen as a Target to Characterize Immunomodulatory Effects of Down-Stream Processed Cyberlindnera jadinii Yeasts in Atlantic Salmon Exposed to a Dietary Soybean Meal Challenge - Morales-Lange, Byron; Agboola, Jeleel Opeyemi; Hansen, Jon Øvrum; Lagos, Leidy; Øyås, Ove; Mercado, Luis; Mydland, Liv Torunn; Øverland, Margareth (Frontiers in Immunology, 2021)
Aquaculture feeds have changed dramatically from being largely based on fishmeal (FM) towards increased use of plant protein sources, which could impact the fish's immune response. In order to characterize immunomodulatory properties of novel functional ingredients, this study used four diets, one based on FM, a challenging diet with 40% soybean meal (SBM), and two diets containing 40% SBM with 5% of Cyberlindnera jadinii yeast exposed to different down-stream processing conditions: heat-inactivated (ICJ) or autolysation (ACJ). The immunomodulatory effects of the diets were analyzed in the spleen of Atlantic salmon after 37 days of feeding using a transcriptomic evaluation by RNA sequencing (RNA-seq) and the detection of specific immunological markers at the protein level through indirect Enzyme-linked Immunosorbent Assay (indirect ELISA). The results showed that SBM (compared to FM) induced a down-regulation of pathways related to ion binding and transport, along with an increase at the protein level of pro-inflammatory cytokines such as tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ). On the other hand, while ICJ (compared to FM-group) maintain the inflammatory response associated with SBM, with higher levels of TNFα and IFNγ, and with an upregulation of creatine kinase activity and phosphagen metabolic process, the inclusion of ACJ was able to modulate the response of Atlantic salmon compared to fish fed the SBM-diet by the activation of biological pathways related to endocytosis, Pattern recognition receptor (PPRs)-signal transduction and transporter activity. In addition, ACJ was also able to control the pro-inflammatory profile of SBM, increasing Interleukin 10 (IL-10) levels and decreasing TNFα production, triggering an immune response similar to that of fish fed an FM-based diet. Finally, we suggest that the spleen is a good candidate to characterize the immunomodulatory effects of functional ingredients in Atlantic salmon. Moreover, the inclusion of ACJ in fish diets, with the ability to control inflammatory processes, could be considered in the formulation of sustainable salmon feed.